Peran Literasi Digital Dalam Mencegah Hoax Pada Siswa SMA - Aster Pujaning Ati (Jurnal Ilmiah Wahana Pendidikan, 2019)
Changing times are very fast, it can change all sides of human life. Complete and complicated information is very swift, difficult for the students to stop. Very much information is increasingly difficult to distinguish, which is true and mere figment. Today's students are digital millennials who have boundaries to sort out which information is correct. The still low level of information literacy among students impacts the plagiarism of copyrighted works. Therefore, teachers as educators and school stakeholders as educational staff must have information literacy skills that can be used for students in information literacy skills in the digital age. The purpose of this study, to see the extent of the role of digital literacy in preventing false news (hoax). The data was taken from a questionnaire given to 40 high school students. Congratulations on this research, it appears that students still lack understanding of digital literacy. To ward off lies, students will continue to understand, access all information, must be selective and wise. Digital literacy is activated from the family, and supervision of parents and teachers.